2022
DOI: 10.3390/cancers14040953
|View full text |Cite
|
Sign up to set email alerts
|

Everything Comes with a Price: The Toxicity Profile of DNA-Damage Response Targeting Agents

Abstract: Targeting the inherent vulnerability of cancer cells with an impaired DNA Damage Repair (DDR) machinery, Poly-ADP-Ribose-Polymerase (PARP) inhibitors have yielded significant results in several tumor types, eventually entering clinical practice for the treatment of ovarian, breast, pancreatic and prostate cancer. More recently, inhibitors of other key components of DNA repair, such as ATR, CHK1 and WEE1, have been developed and are currently under investigation in clinical trials. The inhibition of DDR inevita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 142 publications
(325 reference statements)
0
18
0
Order By: Relevance
“… 48 , 49 While there were no instances of pneumonitis recorded in the TRITON2 study, studies have shown that PARP inhibitors (for example, Olaparib) lead to a significantly increased risk of this and other respiratory toxicities. 28 , 50 Finally, while no patients reported myelodysplastic syndrome (as seen in some trials with rucaparib), one patient died due to acute myeloid leukemia after discontinuing Olaparib (an event also recorded with rucaparib trials). One patient also developed a glioma during the study.…”
Section: Comparison With Other Parp Inhibitorsmentioning
confidence: 99%
“… 48 , 49 While there were no instances of pneumonitis recorded in the TRITON2 study, studies have shown that PARP inhibitors (for example, Olaparib) lead to a significantly increased risk of this and other respiratory toxicities. 28 , 50 Finally, while no patients reported myelodysplastic syndrome (as seen in some trials with rucaparib), one patient died due to acute myeloid leukemia after discontinuing Olaparib (an event also recorded with rucaparib trials). One patient also developed a glioma during the study.…”
Section: Comparison With Other Parp Inhibitorsmentioning
confidence: 99%
“…As mentioned, PARPis were demonstrated to be clinically effective, with acceptable tolerability and safety, in a specific range of solid tumors, which led to FDA and European Medicines Agency (EMA) approval of Olaparib, Rucaparib, Niraparib, and Talazoparib [ 31 , 290 ]. However, a consolidated body of evidence from studies of PARPi in patients has identified several adverse events and specific indications for their prevention, monitoring, and management [ 291 , 292 , 293 , 294 ]. PARPi display several on- and off-target toxicities, with hematological and gastrointestinal toxicities among the most common adverse events.…”
Section: Liabilities Upon Treatment With Ddr Inhibitorsmentioning
confidence: 99%
“…PARPi display several on- and off-target toxicities, with hematological and gastrointestinal toxicities among the most common adverse events. Pneumonitis and therapy-related myeloid neoplasias (t-MN), such as AML and myelodysplastic syndromes (MDS), have been reported with PARPi, but despite their rare frequency, they are potentially life-threatening, often fatal, and deserve particular attention due to their severity [ 291 ]. The t-MN is typically a late complication of some chemo- and radiotherapy, and the subtype and latency period are usually treatment-dependent [ 295 ].…”
Section: Liabilities Upon Treatment With Ddr Inhibitorsmentioning
confidence: 99%
“…Theoretically, such combinations should improve fractional cell kill and, by extension, clinical effectiveness. However, impairing DNA repair in other rapidly proliferating tissues, such as bone marrow and gastrointestinal mucosa, will result in increased toxicity to these cells and potential life-threatening complications, limiting the utility of such combinatorial therapeutic approaches [40,41]. This is evidenced clinically in trials of MGMT inhibitors and more recently, PARP inhibitors (PARPi) and other DNA repair inhibitors, in combinations with chemotherapy [41][42][43].…”
Section: Dna Repair and Cancermentioning
confidence: 99%